Salt Trading in Deli: Relationship between Karo and Coastal Area in 19th Century - Suprayitno Suprayitno; Ratna Ratna; Handoko Handoko (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
In the East Coast region of Sumatra trade patterns between inland and coastal areas have occurred since the pre-colonial period. If we pull back, the Coastal region and the interior have been trading since the 14th century; this can be seen from the archaeological findings of ancient foreign ceramics in Kabanjahe. In the 19th century, orientlists have stepped on East Sumatra. In their visits and reports, orientalists say that there has been a trade relationship between the people in the community with the coastal community. This indicates that the trade relations of the world’s deep trade with thesis continue to be continued. The role of the inland region is to supply commodities to the coastline; we can interpret that in the coastal region there are no important commodities produced. This article describes the trade relations that occur in the past. This is useful for the flexi trade system of the former with the present. How is the relationship between trade in the 19th century between the interior and the coast.